Antiprotozoal activity of South American medicinal plants - Moretti, C.; Sauvain, M.; Fournet, A. (Malaysian Journal of Science, 2000)
South American medicinal plants used in the treatment of leishmaniasis, malaria and chagas diseases were studied for their active components. Methods of selection, collection and identification of plants were briefly discussed.